PENGARUH KOMITMEN ORGANISASI DAN KOMITMEN PROFESIONAL TERHADAP KEPUASAN KERJA AUDITOR, STRES PERAN SEBAGAI VARIABEL MODERATING PADA KANTOR AKUNTAN PUBLIK (Studi Empiris Pada Kantor Akuntan Publik Di Semarang Dan Solo) - Hernu Dhiandari, 08.05.52.0136; Kartika, Andi (Students' Journal of Accounting and Banking, 2016)
This research was conducted in Semarang and Solo with respondents auditors working on a public accounting firm in Semarang and Solo. In this study, sampling was done by convenience sampling method (the sample selection based on ease) with a sample of 61 people. Data collected by questionnaire submitted directly. Analysis of data using multiple regression moderating variable . Results of the analysis of individual test shows that role conflict and role ambiguity is not a moderate variable. The conclusion that the variable organizational commitment, professional commitment variables, variables of role conflict and role ambiguity variables simultaneously significant effect on job satisfaction while partial (individual) professional commitment significant effect on job satisfaction.Keywords: Organizational Commitment, Professional Commitment, Job Satisfaction, Role Conflict, Role Ambiguity